2018
DOI: 10.1039/c8dt01790e
|View full text |Cite
|
Sign up to set email alerts
|

CsPbBr3 perovskite quantum dots/ZnO inverse opal electrodes: photoelectrochemical sensing for dihydronicotinamide adenine dinucleotide under visible irradiation

Abstract: All-inorganic perovskite quantum dots (PQDs) have attracted tremendous attention due to their extraordinary optical properties, especially CsPbBr3 QDs with their high stability and photoluminescence efficiency. However, studies investigating the biosensing capabilities of PQDs are still limited. In this work, we designed a visible -light-triggered photoelectrochemical (PEC) sensor based on CsPbBr3 QDs for the first time. The immobilized three-dimensional (3D) ZnO inverse opal photonic crystals (IOPCs) were app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…On the other hand, the good optoelectronic properties of CsPbBr 3 have found other applications such as lightemitting diodes (LEDs), photodetectors, photo-electrochemical sensing and water splitting, photocatalysis for pollutants degradation, CO 2 reduction and organic synthesis, among others. [28][29][30][31][32][33][34][35][36][37] CsPbBr 3 based PSCs remains an interesting material for photovoltaics and other optoelectronic applications due to its high stability under ambient conditions. The absence of organic cations in this perovskite means that no glovebox is strictly required and freshly made CsPbBr 3 films are usually quite robust.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the good optoelectronic properties of CsPbBr 3 have found other applications such as lightemitting diodes (LEDs), photodetectors, photo-electrochemical sensing and water splitting, photocatalysis for pollutants degradation, CO 2 reduction and organic synthesis, among others. [28][29][30][31][32][33][34][35][36][37] CsPbBr 3 based PSCs remains an interesting material for photovoltaics and other optoelectronic applications due to its high stability under ambient conditions. The absence of organic cations in this perovskite means that no glovebox is strictly required and freshly made CsPbBr 3 films are usually quite robust.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were also obtained by Yang et al, who demonstrated that the carbon nanotube with high conductivity could accelerate charge separation and transfer. Inspired by this, Zhu et al immobilized CsPbBr 3 QDs in 3D ZnO IOPCs, which possessed higher charge mobility and better conductivity than TiO 2 , to detect dihydronicotinamide adenine dinucleotide (NADH) in phosphate buffer saline solution and serum. Like the above‐mentioned CsPbBr 1.5 I 1.5 /TiO 2 IOPCs electrode, the photocurrent response of the obtained CsPbBr 3 /ZnO IOPCs composite was also improved to the visible light region ranging from 400 to 560 nm.…”
Section: Photoelectrochemical Applications Of Ihpqdsmentioning
confidence: 99%
“…As a result, the interfacial recombination may increase. For example, compared to the CsPbBr 1.5 I 1.5 /TiO 2 IOPCs electrode, CsPbBr 3 /ZnO IOPCs composite demonstrated higher PEC performance . Thus, employing encapsulation layer with excellent conductivity (such as ZnO, SnO 2 ) may further improve the PEC performance.…”
Section: Photoelectrochemical Applications Of Ihpqdsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the photoelectrochemical (PEC) detection method is based on the photo-to-charge conversion process. 13 The light and electricity are used for the sensor excitation and detection respectively, 14 indicating that PEC detection technology has high sensitivity. 15 Moreover, the PEC method has attracted widespread concern because of its low cost and convenient.…”
Section: Introductionmentioning
confidence: 99%